WHAT A FIRM TAKES TO COMPETE IN CONDITIONS OF ECONOMIC ADVERSITY - Muyanja Sseyonga (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
This article attempts to identify the key factors that underpin thesuccess of firms in conditions of economic distress. Such factors encompass astute management with the skill and experience in a variety of competitive moves and maneuvers; adoption of low-cost -low price strategies; more use of scenario planning rather than mere replication of past company actions; sufficient liquidity to exploit opportunities availed by economic downturn;and exploiting the advantages of knowledge management. Better incorporation of information technology, proper use of currency risk management methods, smart globalization that incorporates both government and non-government elements, favors the formation of joint ventures with local businessmen, and investment of ample time in the understanding the customs, values, and traditions of local societies elevate company’s com-petitive advantages over rivals which enhances the company’s capacity to deal with economic distress. It is incontrovertible, however, that the success of firms must be backed by strong and appropriate macroeconomic management by governments with respect to fiscal, monetary and trade policies.